2021
DOI: 10.48144/prosiding.v1i.960
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Suami dengan Pemberian ASI Eksklusif : Literature Review

Abstract: Global study “The Lancer Breastfeeding Series” 2016 explains that infant mortality due to infection reaches 88% in infants aged less than three months, while 82% of children get sick because they do not receive exclusive breastfeeding. Exclusive breastfeeding can reduce infant mortality due to infection. Several factors that affect exclusive breastfeeding are the mother, the infant, and support factors. One of the sources of support that can affect exclusive breastfeeding is the husband’s support. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(7 reference statements)
0
4
0
3
Order By: Relevance
“…The concept of scientific argumentation has subsequently become an attraction among policymakers in various countries (Admoko et al, 2021;Henderson et al, 2018). Scientific argumentation has also become a central issue in various studies and research related to science learning in recent years (Kim & Roth, 2018;Nazidah et al, 2022;Valero Haro et al, 2019;Wang et al, 2022;Wulandari et al, 2019). These studies mostly focus on implementing effective learning designs or strategies in improving students' scientific argumentation skills (Ault et al, 2015;Henderson et al, 2018;Osborne et al, 2019;Ping et al, 2020;Sampson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of scientific argumentation has subsequently become an attraction among policymakers in various countries (Admoko et al, 2021;Henderson et al, 2018). Scientific argumentation has also become a central issue in various studies and research related to science learning in recent years (Kim & Roth, 2018;Nazidah et al, 2022;Valero Haro et al, 2019;Wang et al, 2022;Wulandari et al, 2019). These studies mostly focus on implementing effective learning designs or strategies in improving students' scientific argumentation skills (Ault et al, 2015;Henderson et al, 2018;Osborne et al, 2019;Ping et al, 2020;Sampson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Results: The results of the statistical test showed that there was a correlation between the husband's support received by the mother and exclusive breastfeeding with a p-value (0.015) < alpha (0.05). This indicates that there is a relationship between the husband's support received by the mother and exclusive breastfeeding (Wulandari & Nurlaela, 2021).…”
Section: The Effect Of Husband's Support On Exclusive Breastfeeding I...mentioning
confidence: 96%
“…of Nutrients Through Exclusive Breastfeeding to Babies and Lack of Stimulation Can Result in the Risk of Stunting. Considering the many benefits that can be obtained by giving exclusive breast milk to babies for 6 months, the World Health Organization United Nations Children's Fund (UNICEF) and WHO recommends that babies born only receive breast milk from their mothers for 6 months (Wulandari, 2021).…”
Section: Lackmentioning
confidence: 99%